消失或加劇的社會距離？新型冠狀病毒疫情下 課程與教學數位化面臨的挑戰與契機 Eliminating or Widening Social Distance? The Challenges and Opportunities of a Digitalized Curriculum and Instruction During the COVID-19 Global Pandemic - 蔡瑞君 Jui-Chun Tsai (Journal of Curriculum Studies, 2020)
正當新型冠狀病毒疫情對世界造成極大衝擊之際，為因應防疫所需，保持社交距離的政策卻意外點燃課程與教學加速數位化的契機，遠距線上課程在疫情期間被 視為是延續學校教育的良方。本研究旨在探討疫情下課程與教學數位化帶來的契機及潛在問題，除了討論課程與教學數位化及更開放的教育之可能外，也檢視疫情下 推行線上課程時的困境，並提出其中潛藏的爭論議題。此外，本研究也省思社交距離後的疫後世界可能加劇的社會不平等結構問題，最後提出結論與建議。 While the world suffers from the COVID-19 global pandemic, the policy related to social distancing measures unexpectedly stimulated an enormous growth of digitalized curriculum and instruction. Online education is seen as an effective solution to reduce the impact of learning loss caused by distancing measures put in place because of COVID-19. This article aims to investigate the opportunities, challenges, and problems related to a transition to digital curriculum and instruction during the COVID-19 global pandemic. Digitalized curriculum and instruction create possibilities to a more open education system, however, there are disadvantages and concerns worth addressing. One major cause for concern is the gap in social inequalities created by distance learning. Based on the findings from the research, conclusions and suggestions for further research are proposed.